An ecological latent class model of adolescent risk and protective factors: Implications for substance use and depression prevention. (July 2021) - Bayly, Benjamin L.; Vasilenko, Sara A.
To provide a comprehensive view of the unique contexts shaping adolescent development in the U.S., we utilized latent class analysis (LCA) with indicators of risk and protection across multiple domains (family, peers, school, neighborhood) and examined how latent class membership predicted heavy episodic drinking, illicit substance use, and depression in adolescence and 6 years later when participants were young adults. Data came from Wave 1 (W1) and Wave 3 (W3) of the nationally representative U.S.-based Add Health study ( N = 6, 649; M age W1 = 14.06; M age W3 = 20.38; 53.8% female; 56.1% White/European American, 22.8% Black/African American, 9.5% Hispanic, 6.7% Biracial, Asian or Pacific Islander 4.2%, American Indian/Native American 0.7%). A six-class solution was selected with classes named: Two Parent: Low Risk, Two Parent: Relationship Risks, Two Parent: Neighborhood Risks, Single Parent: Low Risk, Single Parent: Relationship Risks, and Single Parent: Multidimensional Risk. Subsequent analyses suggested that adolescent social relationships are particularly important for prevention interventions as the classes marked by substance using peers and a lack of closeness to parents and teachers in adolescence (Two Parent: Relationship Risks and Single Parent: Relationship Risks) had consistently poorer outcomes in adolescence and young adulthood.